Cast application of four weeks' duration significantly affects hair length, diameter and density. (April 2014) - Chairerg, Piyanuch; Tantavisut, Saran; Tanavalee, Aree; Tuangjaruwinai, Wirach; Panchaprateep, Ratchathorn; Asawanonda, Pravit
<x xml:space="preserve">Abstract</x> Background: Localized hypertrichosis following cast application has been recorded, yet no studies characterized these changes systematically. Objective: To evaluate changes of hair length, diameter and density on the legs in patients after cast application. Materials and methods: Patients with leg injuries and cast application of at least 4 weeks' duration were included in the study. Immediately after cast removal, hair sampling was taken from both legs; cast and control sides. Hair length and diameter were measured by Olympus microscope software. Patients were also analyzed for global changes by three blinded dermatologists. Results: Fourteen patients, seven of whom were male, were included in this study. On the cast side, both hair length and diameter were significantly greater than the control side (p < 0.001). Subjective evaluations by three blinded dermatologists agreed well with objective measurements and also demonstrated an increase in overall density. Degrees of hair changes did not correlate with the distance from injury sites. Conclusion: Cast application of at least 4 weeks' duration significantly stimulates hair growth in a diffuse pattern. This could possibly lead to novel therapeutic approaches for different types of alopecias.